A core set of risk factors in individuals at risk of rheumatoid arthritis: a systematic literature review informing the EULAR points to consider for conducting clinical trials and observational studies in individuals at risk of rheumatoid arthritis - Daniel Aletaha; Kulveer Mankia; Paul Emery; Deshire Alpizar-Rodriguez; Andreas Kerschbaumer; Andrea Di Matteo; Heidi Siddle; Joel Kerry (RMD Open)
Background There is significant interest in determining risk factors in individuals at risk of rheumatoid arthritis (RA). A core set of risk factors for clinical arthritis development has not been defined.Methods A literature search and systematic literature review (SLR) was conducted to identify risk factors in individuals at risk of RA using Medline, Embase, PubMed and Central databases.Results 3854 articles were identified by the literature search. After screening of titles, 138 abstracts were reviewed and 96 articles finally included. Fifty-three articles included data on risk factors including autoantibodies, subclinical inflammation on imaging, clinical features, serum and cellular biomarkers and genetic markers. Risk factors were dependent on the at-risk population. There was good evidence for serum anticitrullinated protein antibodies (ACPA) levels, as risk factors for arthritis in all at-risk populations (n=13 articles). Subclinical inflammation on ultrasound (n=12) and MRI (n=6) was reported as a risk factor in multiple studies in at-risk individuals with musculoskeletal (MSK) symptoms and undifferentiated arthritis (UA). Clinical features were reported as a risk factor in at-risk individuals with MSK symptoms and UA (n=13). Other risk factors, including serum and cellular markers were less frequently reported.Conclusions Risk factors for arthritis development in RA are specific to the at-risk population. Serum ACPA confers risk in all populations; subclinical inflammation on imaging and clinical features confer risk in at-risk individuals with MSK symptoms. This SLR informed the EULAR taskforce for points to consider on conducting clinical trials and studies in individuals at risk of RA.